Non-invasive Brain and Spinal Stimulation for Pain and Related Symptoms in Multiple Sclerosis: A Systematic Review - Zucchella, Chiara; Mantovani, Elisa; De Icco, Roberto; Tassorelli, Cristina; Sandrini, Giorgio; Tamburin, Stefano (Frontiers in Neuroscience, 2020)
Background. Neuropathic and nociceptive pain frequently affect patients with multiple sclerosis (MS), with a prevalence close to 90% and significant impact on general health and quality of life. Pharmacological strategies are widely used to treat pain in MS, but their effectiveness and side-effects are controversial. Among non-pharmacological treatments for pain, non-invasive brain and spinal stimulation (NIBSS) has shown promising preliminary results in MS. Objective. Systematic review to investigate the effect of NIBSS for the management of pain in MS. Methods. A literature search using Pubmed, Science Direct and Web of Science was conducted from databases inception to February 21, 2020 for studies assessing the analgesic effect of NIBSS on pain MS. Results. A total of 279 records were title- and abstract-screened, nine were assessed for full text and included. The NIBSS techniques explored were transcranial direct current stimulation (tDCS; N = 5), transcranial magnetic stimulation (rTMS; N = 2), transcranial random noise stimulation (tRNS; N =1), transcutaneous spinal direct current stimulation (tsDCS; N = 1). The targets were the primary motor cortex (M1; N = 4), the left dorsolateral prefrontal cortex (DLPFC; N = 3), the spinal cord (N = 1), unspecified brain target (N = 1). The study designs were randomized (N = 7), open label (N = 1), single case report (N = 1). Despite the differences in study design, target and NIBSS technique that impeded a meta-analysis, all the studies converge in showing a significant improvement of pain after active NIBSS with less consistent effects on other symptoms of the pain-related cluster (depression, fatigue, cognition) and quality of life. Conclusions. Excitatory NIBSS over M1, left DLPFC and spinal cord appear to be the most effective protocols for pain in MS. Open questions include the use of neurophysiological or neuroimaging surrogate outcome measures, the stratification of patients according to the clinical profiles and underlying pathogenetic mechanisms and the combination of NIBSS to pharmacological treatment, neurorehabilitation, or psychotherapy to improve the clinical effect. The duration of the effect to NIBSS and the feasibility and efficacy of telemedicine NIBSS protocols are other open key questions.